IbM USAHA KECAP DAN SAUS PREBIOTIK PEMANFAATAN CHITO-OLIOGOSACCHARIDE (COS) SEBAGAI PREBIOTIK DAN PENGAWET PADA KECAP DAN SAUS - Agnes Sri Harti; Desy Handayani; Hutari Puji Astuti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
UKM ketchup " Tomat Lombok " and UKM sauces " Sinar Mulia " is located in Penusupan street RT 04 RW Penusupan Village , District Kagok Slawi , Tegal city , Central Java Province . UKM ketchup " tomato Lombok " owned by Mr. HS Sumarnoto producing 1400 kg per day , whereas UKM sauce " Sinar Mulia " produces 500 kg of sauce per day . Total waste of two UKM to produce solid waste at 60 kg / day and 3 m3 of liquid waste . In generally produce soy sauce and sauce according to market needs and conventional manufacturing process so it is not durable or easily damaged due to microbial contamination in nature . Spoilage microorganisms in soy sauce is generally proteolytic bacteria or molds. Chito - oligosaccharides synthesis process ( COS ) from shrimp or crab shell waste that is relatively easy , simple ,  so that COS can be used as a prebiotic and a natural preservative and prebiotics for the production of ketchup and sauce  in UKM partner. The integrated COS utilization  ketchup and  sauce  is expected to function as a preservative , a natural prebiotic , antioxidant and adsorbent in wastewater treatment, so that  is expected to provide value -added aspects of the technology , economic and social through halal certificates and patents , which in turn can improve well-being . Keywords : UKM , ketchup and sauce, chito-oligosaccharide, prebiotics, preservatives